European Policies and Arts Management seen from Aristotle’s Theatrical Culture Perspective - Giouli, Ph.D., Virginia M. (Aesthetica Preprint, 2023)
Cultural policies and arts management in modern Europe prove that solely politics can substantiate attempts to defuse power through Aristotle’s idea of theatrical culture. Aristotle, a forerunner of an industrial cultural policy in Europe states that theatrical art ceases to be merely an incantatory procedure aiming to console us for the evils of our time and becomes a cognitive process. Aristotle’s idea of staged myths used in this way stresses how little can be done as regards the realisation of some such policies and management, if we ignore the importance of theatre as a political institution.